Revealing the Salmo salar NLRP3 Inflammasome: Insights from Structural Modeling and Transcriptome Analysis - Waldo Acevedo; Rodrigo Morán-Figueroa; Luis Vargas-Chacoff; Francisco J. Morera; Juan Pablo Pontigo (International Journal of Molecular Sciences, 2023)
The NLRP3, one of the most heavily studied inflammasome-related proteins in mammals, remains inadequately characterized in Atlantic salmon ( Salmo salar ), despite the significant commercial importance of this salmonid. The NLRP3 inflammasome is composed of the NLRP3 protein, which is associated with procaspase-1 via an adapter molecule known as ASC. This work aims to characterize the Salmo salar NLRP3 inflammasome through in silico structural modeling, functional transcript expression determination in the SHK-1 cell line in vitro, and a transcriptome analysis on Atlantic salmon . The molecular docking results suggested a similar arrangement of the ternary complex between NLRP3, ASC, and caspase-1 in both the Atlantic salmon and the mammalian NLRP3 inflammasomes. Moreover, the expression results confirmed the functionality of the SsNLRP3 inflammasome in the SHK-1 cells, as evidenced by the lipopolysaccharide-induced increase in the transcription of genes involved in inflammasome activation, including ASC and NLRP3. Additionally, the transcriptome results revealed that most of the inflammasome-related genes, including ASC, NLRP3, and caspase-1, were down-regulated in the Atlantic salmon following its adaptation to seawater (also known as parr–smolt transformation). This is correlated with a temporary detrimental effected on the immune system. Collectively, these findings offer novel insights into the evolutionarily conserved role of NLRP3.